Utility of broad-range 16S rRNA PCR assay versus conventional methods for laboratory diagnosis of bacterial endophthalmitis in a tertiary care hospital. Issue 1 (12th October 2018) - Mishra, Deepanshi; Satpathy, Gita; Chawla, Rohan; Venkatesh, Pradeep; Ahmed, Nishat Hussain; Panda, Subrat Kumar
Abstract : Background: Endophthalmitis, a sight-threatening intraocular infection, can be of postsurgical, post-traumatic or endogenous origin. Laboratory diagnosis-based appropriate therapy can be vision-saving. Conventional culture-based laboratory diagnosis takes time and lacks sensitivity. In this study a broad-range PCR assay was assessed against conventional and automated culture methods in vitreous specimens for accurate microbiological diagnosis. Aims: To use broad-range PCR assay targeting 16S ribosomal RNA (rRNA) region of bacteria and to assess its performance vis-à-vis conventional and automated culture methods in the laboratory diagnosis of endophthalmitis. Methods: Vitreous specimens from 195 patients with clinically diagnosed endophthalmitis were processed for classical and automated culture methods, antimicrobial sensitivity and broad-range PCR assay targeting 762 bp region of 16S rRNA followed by nucleotide sequencing by Sanger's method. Causative agents were identified from the nucleotide sequences analysed against the GenBank database, and organisms were identified using the Clinical and Laboratory Standards Institute (CLSI) MM18A guidelines. Results: Bacteria could be detected from 127 (65.13%) of the 195 vitreous specimens by broad-range PCR assay; bacterial isolation was possible from 17 (8.7%) and 60 (30.76%) of these specimens by conventional and automated culture methods, respectively (p<0.0001). PCR assay could detect two uncultured bacterium, and in five cases the bacterial identity could not be determined from NCBI database matching. Conclusion: Broad-range PCR assay could provide definitive microbial diagnosis within 24 hours in significantly more patients (p<0.0001). Some rare organisms could be detected, useful in treatment modalities. Automated culture was significantly more sensitive than conventional culture.